A Note on a Planning Horizon Model of Cash Management - Sethi, Suresh P. (Journal of Financial and Quantitative Analysis, 1971)
The problem of cash management, in its simplest form, is to formulate decision rules which control the level of a firm's cash balance to meet its demands for cash at minimum total discounted cost. Control is achieved by transacting securities for cash. The cost of control is the commission expense [13]. Optimality depends on balancing excess opportunity costs of holding balances which are too large and having excess buying and selling costs (to meet cash obligations) of balances which are too small.